N‐acetyl‐l‐tyrosine is an intrinsic triggering factor of mitohormesis in stressed animals. (2nd March 2020) - Matsumura, Takashi; Uryu, Outa; Matsuhisa, Fumikazu; Tajiri, Keiji; Matsumoto, Hitoshi; Hayakawa, Yoichi
Abstract: Under stress conditions, mitochondria release low levels of reactive oxygen species (ROS), which triggers a cytoprotective response, called "mitohormesis". It still remains unclear how mitochondria respond to stress‐derived stimuli and release a low level of ROS. Here, we show that N ‐acetyl‐l ‐tyrosine (NAT) functions as a plausible intrinsic factor responsible for these tasks in stressed animals. NAT is present in the blood or hemolymph of healthy animals, and its concentrations increase in response to heat stress. Pretreatment with NAT significantly increases the stress tolerance of tested insects and mice. Analyses using Drosophila larvae and cultured cells demonstrate that the hormetic effects are triggered by transient NAT‐induced perturbation of mitochondria, which causes a small increase in ROS production and leads to sequential retrograde responses: NAT‐dependent FoxO activation increases in the gene expression of antioxidant enzymes and Keap1. Moreover, we find that NAT represses tumor growth, possibly via the activation of Keap1 . In sum, we propose that NAT is a vital endogenous molecule that could serve as a triggering factor for mitohormesis. Synopsis: The metabolite N ‐acetyl‐l ‐tyrosine functions as an endogenous triggering factor for mitohormesis in mammals and insects. The low level of ROS released by mitochondria in distress has been pointed out to be important for hormesis induction, which is called 'mitohormesis'. N ‐acetyl‐l ‐tyrosine is present in the blood or hemolymph of healthy animals, and its concentrations increase in response to heat stress. N ‐acetyl‐l ‐tyrosine transiently perturbs mitochondria, which causes a small increase in ROS production and leads to trigger mitohormesis. Abstract : The metabolite N ‐acetyl‐l ‐tyrosine functions as an endogenous triggering factor for mitohormesis in mammals and insects.